Antimicrobial activity of four cationic peptides immobilised to poly-hydroxyethylmethacrylate. Issue 4 (20th April 2016) - Dutta, Debarun; Kumar, Naresh; D. P. Willcox, Mark
Abstract: The objective of this study was to immobilise and characterise a variety of antimicrobial peptides (AMPs) onto poly-hydroxyethylmethacrylate (pHEMA) surfaces to achieve an antibacterial effect. Four AMPs, viz. LL-37, melimine, lactoferricin and Mel-4 were immobilised on pHEMA by 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) which assisted covalent attachment. Increasing concentrations of AMPs were immobilised to determine the effect on the adhesion of Pseudomonas aeruginosa and Staphylococcus aureus . The AMP immobilised pHEMAs were characterised by X-ray photoelectron spectroscopy (XPS) to determine the surface elemental composition and by amino acid analysis to determine the total amount of AMP attached. In vitro cytotoxicity of the immobilised pHEMA samples to mouse L929 cells was investigated. Melimine and Mel-4 when immobilised at the highest concentrations showed 3.1 ± 0.6 log and 1.3 ± 0.2 log inhibition against P. aeruginosa, and 3.9 ± 0.6 log and 2.4 ± 0.5 log inhibition against S. aureus, respectively. Immobilisation of LL-37 resulted in up to 2.6 ± 1.0 log inhibition against only P. aeruginosa, but no activity against S. aureus . LFc attachment showed no antibacterial activity. Upon XPS analysis, immobilised melimine, LL-37, LFc and Mel-4 had 1.57 ± 0.38%, 1.13 ± 1.36%, 0.66 ± 0.47% and 0.73 ± 0.32% amide nitrogen attached to pHEMA compared to 0.12 ± 0.14% in the untreated controls. Amino acid analysis determined that the total amount of AMP attachment to pHEMA was 44.3 ± 7.4 nmol, 3.8 ± 0.2 nmol, 6.5 ± 0.6 nmol and 48.9 ± 2.3 nmol for the same peptides respectively. None of the AMP immobilised pHEMA surfaces showed any toxicity towards mouse L929 cells. The immobilisation of certain AMPs at nanomolar concentration to pHEMA is an effective option to develop a stable antimicrobial surface.